Zosteriform impetigo: Wolf’s isotopic response in a cutaneous immunocompromised district - Philip R. Cohen (Mattioli1885, 2015)
Background: Impetigo can result from Staphylococcus aureus (S. aureus). Wolf’s isotopic response is the occurrence of a new cutaneous disorder at the site of a previously healed disease. A cutaneous immunocompromised district is an area of skin that is more vulnerable than the rest of the individual’s body.